Vergleich technischer Implementierungen für GridFlow-Systeme - Nobbe, Christoph (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2015)
With the compact warehousing of goods, the main aim is to achieve the highest possible space utilisation rate. Automated compact warehouses only become profitable once they exceed a particular size and throughput. The alternative is to opt for low-cost ground storage systems. This book will examine various technical implementation methods that can be used to realise the GridFlow principle.